Characteristics of Indicators of Professional and Personal Development of Modern Leaders of Law Enforcement Agencies - BOIKO-BUZYL, YULIIA; OKHRIMENKO, IVAN; SPRYNCHUK, SVITLANA; OKHRIMENKO, SVITLANA; BLOSHCHYNSKYI, IHOR; PIANKIVSKA, LIUDMYLA (The journal of contemporary issues in business and government, 2021)
The importance of studying the professional and personal development of management level of law enforcement officers is due to the fact that scientific research today must take into account the constant complexity and updating of the content of official activities and the growing role of the human factor in a new, technically and information-intensive reality. The leader of the system of police organizations must be a professional, a leader who directs the activities of subordinate personnel by personal example, is ready for balanced risk, decision-making and self- development. Therefore, a research that would relate to the essential content of professional and personal development of a specialist becomes relevant, and the presented research is devoted to these aspects. The purpose of the research is to study the psychological characteristics of professional and personal development of leaders of law enforcement agencies in a comparative analysis with employees who do not perform managerial functions. The research is based on the use of a number of methods of psychological diagnosis, with the help of which 844 people, including 385 leaders and 459 employees of law enforcement agencies were examined. The obtained results were processed using the methods of mathematical statistics. It is proved that the indicators of professional and personal development of management level representatives of law enforcement agencies differ from similar indicators of non-leaders in terms of quality and content, which is focused primarily on the implementation of managerial functions. Experimental data will contribute to the improvement of management theory and practice within the system of police organizations functioning.